1987
DOI: 10.1159/000265497
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Behavior in Long-Standing Branch Retinal Vein Occlusion

Abstract: The aim of our study was to evaluate the fibrinolytic system in patients with retinal branch vein occlusion (RVO). The following tests were carried out: prothrombin time, partial thromboplastin time (PTT), fibrinogen degradation products, euglobulin lysis time, fibrinogen, pasminogen, antithrombin III, α2-antiplasmin and α2-macroglobulin. Comparing the results of patients with those of normal controls, only the fibrinogen increase and PTT shortening were significantly different. All other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Trope demonstrated decreased levels of AT III in the retinal vein occlusion group (Trope et al 1983). Patrassi found nor-mal AT III levels in patients with long standing branch retinal vein occlusion (Patrassi et al 1987) and Gottlieb found normal PC, PS and AT III levels in young adults with CRVO (Gottlieb et al 1998). Williamson reported increased mean AT III and decreased mean activated protein C in patients with CRVO than in controls (Williamson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Trope demonstrated decreased levels of AT III in the retinal vein occlusion group (Trope et al 1983). Patrassi found nor-mal AT III levels in patients with long standing branch retinal vein occlusion (Patrassi et al 1987) and Gottlieb found normal PC, PS and AT III levels in young adults with CRVO (Gottlieb et al 1998). Williamson reported increased mean AT III and decreased mean activated protein C in patients with CRVO than in controls (Williamson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Increased blood viscosity measured as increases in hematocrit, plasma fibrinogens, and immunoglobulins was implicated in the etiology of venous occlusions [9,10,[43][44][45]. Appiah and Trempe [46] found an association between the elevated erythrocyte sedimentation rate and CRVO.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological dysfunction, such as increased plasma fibrinogen and disruption of the thrombosis-fibrinolysis balance, have been implicated in the development of RVO . Increased fibrinogen has been associated with RVO in several clinical reports (Lip et al, 1998;Patrassi et al, 1987;Peduzzi et al, 1986). An increasing number of studies have sought to establish an association between RVO and thrombophilic abnormalities.…”
Section: Risk Factors Of Rvomentioning
confidence: 97%